Conceptual metaphors and image construction of China in the space probe reports of China Daily: a social cognitive approach - Li, Xueying; Lu, Danyun (Frontiers in Psychology, 2023)
The success of Shenzhou XIII and Chang'e-5 mission became a milestone in China's aerospace history and represented China's latest attempt to contribute to international space industry, which greatly promoted the China's national image. However, rare studies have examined the image construction in aerospace field. Thus, this study takes conceptual metaphors as the guiding theory and studies conceptual metaphors in China Daily news release on Chang'e-5 and Shenzhou XIII from 2008 to 2021. It focuses on the types of metaphors used, the semantic features of the metaphors, and the characteristics of Chinese images in aerospace field. It is found that China Daily widely uses conceptual metaphors in its news release on space probe, which mainly includes 11 conceptual metaphor categories such as “endeavor,” “great significance,” “time” and “journey,” and 20 types of conceptual metaphor subcategories, all of which are working together to construct the image of China in aerospace industry, which is characterized with the following features: a dream-building action with lofty goals, an enterprising action which represents the prosperity and progress of China, an exploratory action that is constantly forging ahead and pursuing, a leading action that opens a new chapter and leads a new journey, a braving action which dares to be the first to live in the space, and an achieving action to create a community with a shared future for mankind.